Japanese restaurants in Singapore : an industrial analysis. - Cheng, Nien Haw. (2008)
This paper attempts to explore the critical success factors of Japanese restaurants in Singapore. It encompasses an environmental analysis, SWOT analysis and a perceptual mapping of the 3 participating restaurants.